The Influence of Competency and Work Motivation on the Employee’s Performance of Public Works and Spatial Planning Service - Wanggara, Iyangga; Helmi, Sulaiman; Hasmawaty, Hasmawaty (Journal of Social Work and Science Education, 2024)
The Department of Public Works and Spatial Planning has regional government duties in the fields of roads, bridges, irrigation, and spatial planning. The research method used in this research is a quantitative approach with a non-probability sampling method, namely purposive sampling, which is defined as taking samples from designated subjects based on certain characteristics. The selected prospective respondents were employees of the Public Works and Spatial Planning Department of Pagar Alam City. The data analysis technique used is Partial Least Square Structural Equation Modeling (PLS-SEM) using the SMARTPLS application. Based on the results of the hypothesis analysis test, several things can be concluded from this research, namely, Competence has a positive and significant effect on Employee Performance, Work Motivation has a positive effect and significant on Employee Performance, Work Motivation and Competence has a positive and significant effect on Employee Performance.